2021
DOI: 10.1017/s1478951521000808
|View full text |Cite
|
Sign up to set email alerts
|

Death anxiety in patients with primary brain tumor: Measurement, prevalence, and determinants

Abstract: Objective This study investigated death anxiety in patients with primary brain tumor (PBT). We examined the psychometric properties of two validated death anxiety measures and determined the prevalence and possible determinants of death anxiety in this often-overlooked population. Methods Two cross-sectional studies in neuro-oncology were conducted. In Study 1, 81 patients with PBT completed psychological questionnaires, including the Templer Death Anxiety Scale (DAS). In Study 2, 109 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Perhaps this is because they are caring for patients with poorer prognoses, whose possible lower functional status serves as a reminder of their mortality (Adelbratt and Strang, 2000). Interestingly, this finding is in contrast to reports from patients with PBT, in which there was no association between death anxiety and tumor grade (Loughan et al, 2021). Caregiver death anxiety was not associated with age, race, relationship to the patient, time since diagnosis, tumor type, tumor hemisphere, or treatment type.…”
Section: Correlates Of Death Anxietymentioning
confidence: 55%
See 4 more Smart Citations
“…Perhaps this is because they are caring for patients with poorer prognoses, whose possible lower functional status serves as a reminder of their mortality (Adelbratt and Strang, 2000). Interestingly, this finding is in contrast to reports from patients with PBT, in which there was no association between death anxiety and tumor grade (Loughan et al, 2021). Caregiver death anxiety was not associated with age, race, relationship to the patient, time since diagnosis, tumor type, tumor hemisphere, or treatment type.…”
Section: Correlates Of Death Anxietymentioning
confidence: 55%
“…This finding parallels a study of patients with PBT, where cluster analysis revealed that most patients endorsed high death anxiety but low emotional distress (i.e., symptoms of depression and anxiety) (Loughan et al, 2020). Yet, death anxiety in caregivers was even more prevalent (69%) than what was identified in a previous sample of patients with PBT, which found that 48% of patients endorsed moderate-to-severe death anxiety on the DADDS (Loughan et al, 2021). This finding echoes caregivers' description of their loved one's death as an "all-consuming preoccupation" (Applebaum et al, 2016) and follows a similar pattern of results of other measures of psychological distress, such that caregivers consistently report greater emotional distress than patients with PBT (Petruzzi et al, 2013;Baumstarck et al, 2018;Braun et al, 2021).…”
Section: Prevalence Of Death Anxietymentioning
confidence: 63%
See 3 more Smart Citations